Freedom Writers - DeVito, Danny; Shamberg, Michael; Sher, Stacey; LaGravenese, Richard; Swank, Hilary; Dempsey, Patrick, 1966-; Glenn, Scott, 1942-; Staunton, Imelda, 1956-; Hernandez, April Lee.; Mario, 1986-; Herrera, Kristin; Ngan, Jacklyn; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2007)
A true story about a teacher in a racially divided school who gives her students what they've always needed, a voice. Erin Gruwell comes to a southern California high school bubbling over with naive optimism. She quickly discovers that her unruly classroom is not easily won over by her good intentions. After a few floundering attempts to connect with her students, Gruwell gives them the assignment of keeping journals about their own lives, This assignment is something that the class can bite into with relish. This eventually bonds them together and pushes racial rivalries aside. Draws heavily from the published journals of the real students themselves.
DVD; region 1; widescreen presentation.
Closed-captioned; dialogue in English (Dolby 5.1, Dolby 2.0) or French (Dolby 5.1) with optional English subtitles.
Hilary Swank, Patrick Dempsey, Scott Glenn, Imelda Staunton, April Lee Hernandez, Mario, Kristin Herrera, Jacklyn Ngan, Sergio Montalvo, Jason Finn, Deance Wyatt, Vanetta Smith, Gabriel Chavarria, Hunter Parrish.
Director of photography, Jim Denault ; editor, David Moritz ; music, Mark Isham, RZA ; costume designer, Cindy Evans ; production designer, Laurence Bennett.
Based on the book "The Freedom Writers diary: how a teacher and 150 teens used writing to change themselves and the world around them" by the Freedom Writers and Erin Gruwell.
MPAA rating: PG-13; for violent content, some thematic material and language.
Keywords: Gruwell, Erin -- Drama; Education, Urban -- California -- Drama; Teacher-student relationships -- California -- Drama; Student publications -- California -- Drama; High school students -- California -- Social conditions -- Drama; Urban schools -- California -- Drama; Education, Urban -- California -- Drama; Teacher-student relationship -- California -- Drama; Diaries -- Authorship -- Drama; Student publications -- California -- Drama; High school students -- California -- Drama; High school students -- Social conditions -- Drama; High school students -- Attitudes -- Drama; Feature films; Melodrama; Melodrama -- Feature; Women -- Feature; Youth -- Feature; Video recordings for hard of hearing people; Videodiscs; DVD-Video discs